Worked examples in an introductory programming module - Moura, Isabel Cristina A. A. (2013)
Active learning engages students in programming activities. Instructing novice undergraduates to solve standard programming problems primarily by making them generate the solutions is a form of active learning. As the latter provides little guidance from the instructor it puts a heavy load on these students’ working memory, preventing some of them from learning programming fundamentals. This appears to have happened in the 2009 edition of an introductory programming module at the University of Minho, given its high failure rates. But, the instructor can provide novice undergraduates with superior guidance by making them study and complete programming worked examples. Research in education and cognitive load theory suggests that studying and completing worked examples directs these students’ attention to learning the essential of relations between problem-solving moves by diminishing their working memory load. The empirical studies that were reviewed corroborate such premise. In this chapter we describe how worked examples have been successfully applied to the 2010 edition of that same introductory programming module, reducing its failure rates. The chapter portrays the changes in this module from a program-generation to a program-completion instructional format. The results in terms of success, failure, and dropout are given; and the impact on students’ academic achievements of an implementation that emphasized the completion of programming worked examples is analyzed.